FROM TASKS TO COMMUNICATION: EXPLORING THE IMPACT OF TASK-BASED LANGUAGE TEACHING ON LANGUAGE LEARNING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores Task-Based Language Teaching (TBLT) as a learner-centered approach within modern foreign language education. The paper examines the main theoretical principles underlying TBLT and considers its practical application in classroom contexts. Particular emphasis is placed on the role of tasks in promoting communicative competence, learner motivation, and spoken fluency. The study also reflects on classroom outcomes associated with task-based instruction and discusses the significance of TBLT for contemporary language teaching practice.